Private Non-State Sector Engagement in the Provision of Educational Services at the Primary and Secondary Levels in South Asia : An Analytical Review of Its Role in School Enrollment and Student Achievement - Dahal, Mahesh; Nguyen, Quynh (World Bank, Washington, DC, 2014)
Private (non-state) sector engagement in the provision of educational services at the primary and secondary levels in South Asia has recently undergone remarkable growth. This type of education comes in various forms, such as schools financed and managed by the private sector, schools financed by the government and managed by the private sector, private school vouchers, and tutoring outside the classroom. According to recent household survey data, almost one-third of school-goers aged 6 to 18 years in South Asia go to private schools, with a high concentration in Bangladesh, India, Nepal, and Pakistan. Data for India, Nepal, and Pakistan show that on average, private schools perform at least as well as government schools on student test scores, after controlling for socioeconomic factors, and they do so at significantly lower costs to society. However, student achievement varies greatly across schools of each type, with many weak private schools as well as strong government schools. Substantial, albeit indirect, evidence points to teacher behavior and accountability as an important driver of the effectiveness of private schools. In the long run, however, many factors may play important roles in sustaining the private sector's advantage. Another risk is that overall poor quality in a large government sector may set a low benchmark for the private sector. The findings cast doubt on the effectiveness of government regulations for private schools, given weak institutional capacity. Public-private partnerships with effective accountability mechanisms could leverage both equity and efficiency. Finally, it appears important to understand and customize teaching to the child's individual level.